The Effect of Clinical Factors on the Reversion of Cg05575921 Methylation in Smoking Cessation - Robert Philibert; Steven R. H. Beach; Michelle R. vanDellen; James A. Mills; Jeffrey D. Long (Epigenomes)
Background: Financial Incentive Treatments (FIT) can be effective in the treatment of smoking. However, weaknesses in current biochemical approaches for assessing smoking cessation may hinder its implementation, particularly for management of long-term smoking cessation. The use of cg05575921 methylation assessments could address some of the shortcomings of current self-report and non-self-report methods, but additional information is needed about the speed of methylation reversion as a function of key clinical and demographic variables. Methods: To better understand those relationships, we analyzed data from 3040 subjects from the National Lung Screening Trial (NLST), including 1552 self-reported quitters. Results: Plotting of the data as a function of time since quitting shows that methylation increases approximately 14%, on average, after at least one full year of cessation with a subsequent slow non-linear increase in methylation over the next 14 years. Least Squares Regression modeling shows strong effects of quit time and a modest, yet significant, effect of body mass index (BMI) on the rate of reversion. Prior cigarette consumption characteristics and sex made modest contributions as well, with the latter largely offset by pre-cessation methylation levels. Race and age were not significant factors in the models. Conclusions: When combined with data from prior studies, these analyses of the long-term reversion of cg05575921 methylation will be informative to those considering FIT approaches to incentivizing reversion of cg05575921 as an index of short- and long-term smoking cessation.